2017
DOI: 10.1111/medu.13382
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding premature closure and reaching diagnostic accuracy: some key predictive factors

Abstract: Level of training (i.e. clinical experience) was not associated with accuracy on this task. As faculty clinicians certainly have more knowledge than their junior counterparts, it is important to identify ways in which cognitive factors can lead to more or less persistence and openness, and to teach clinicians how to overcome tendencies associated with error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…A diagnostic decision support system (DDSS) that supports the diagnostic process by generating differential diagnoses from observations provided [ 3 ] is expected to reduce diagnostic errors by reducing cognitive biases and reinforcing physicians’ knowledge. It is said that generating potential diagnoses is a rate-limiting step of differential diagnosis for novice diagnosticians [ 2 ], and their diagnostic accuracy was reported to be associated with the number of generated diagnoses [ 4 ]. Besides, using a simple differential diagnosis checklist, which could remind users of some missed diagnoses, was reported to improve the diagnostic accuracy of medical students [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A diagnostic decision support system (DDSS) that supports the diagnostic process by generating differential diagnoses from observations provided [ 3 ] is expected to reduce diagnostic errors by reducing cognitive biases and reinforcing physicians’ knowledge. It is said that generating potential diagnoses is a rate-limiting step of differential diagnosis for novice diagnosticians [ 2 ], and their diagnostic accuracy was reported to be associated with the number of generated diagnoses [ 4 ]. Besides, using a simple differential diagnosis checklist, which could remind users of some missed diagnoses, was reported to improve the diagnostic accuracy of medical students [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the diagnostic accuracy of clinical examination have found the performance of experienced physicians and students to be comparable [6]. Expert physicians are more often affected by multiple cognitive biases, such as confirmatory bias and premature closure, compared to students, who remain more open to new hypotheses and persist in collecting data [25,26]. Interestingly, while the diagnostic accuracy for individual physicians can be as low as 62.5%, there is a visible increase as the number of physicians involved increases (up to 85.6% for groups of nine physicians) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Functional MRI studies of clinicians during this process showed that highly salient diagnostic information, reducing uncertainty about the diagnosis, rapidly decreased monitoring activity in the frontoparietal attentional network and may contribute to premature diagnostic closure, an important cause of diagnostic errors (Melo et al, 2017). This may be considered a form of diagnosis or recognition related PE signal suppression analogous to the well know phenomenon of repetitive suppression (Blissett & Sibbald, 2017;Bunzeck & Thiel, 2016;Krupat et al, 2017).…”
Section: Core Features Of the Predictive Brain Modelmentioning
confidence: 99%